RESEARCH ON BUILDING FOR DEPENDENCE OF INSULATION PARAMETERS OF THE 6kV GRID WITH THE ENVIROMENT AND STRUCTURAL PARAMETERS OF OPEN-PIT MINES IN THE QUANG NINH AREA - QuocHoan, Tran; Bun, Ho Viet; Nghia, Nguyen Anh (International Journal of Engineering Technologies and Management Research, 2020)
Medium voltage insulation indicators depend on many factors such as environment, length of feeders, numbers of transformers and motors connected on the grid...The values determined by experimental measurements will be used to build up maths distributions. Base on these results, an experimental equation will be formed for determining capacitance and impedance of 6kV grid to ground in QuangNinh open pit coalmines.